Assessing local knowledge of game abundance and persistence of hunting livelihoods in the Bolivian Amazon using consensus analysis - Holt, T. van; Townsend, W.R.; Cronkleton, P. (2010)
We used cultural consensus models to test whether hunters shared perceptions of wildlife abundance and the relative importance of hunting and fishing in a Guarayo indigenous community in the Bolivian Amazon. Results show that highly prized animals that were considered rare are either those with lower reproductive rates and more sensitivity to land use changes and harvest (white-lipped peccary and spider monkey) or those with marked seasonal distribution patterns (barred sorubim and tiger-fish). Rapidly reproducing and resilient species (agouti and armored catfish) were perceived as abundant. More tapirs and red brocket deer were present than predicted by scientific models possibly because hunters were harvesting these species in new forest management areas. Residents identified hunting and fishing among their most important livelihood activities, recognized bush meat and fish as basic food resources, and expected wildlife harvests to be part of their future livelihoods, although market-based livelihoods and domestic replacements for bush meat were reported.